2018
DOI: 10.1111/eva.12608
|View full text |Cite
|
Sign up to set email alerts
|

Turning natural adaptations to oncogenic factors into an ally in the war against cancer

Abstract: Both field and experimental evolution studies have demonstrated that organisms naturally or artificially exposed to environmental oncogenic factors can, sometimes rapidly, evolve specific adaptations to cope with pollutants and their adverse effects on fitness. Although numerous pollutants are mutagenic and carcinogenic, little attention has been given to exploring the extent to which adaptations displayed by organisms living in oncogenic environments could inspire novel cancer treatments, through mimicking th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…There are several other examples of local adaptations in animals to cope with anthropogenic pollution ( Reid et al., 2016 ) ( Whitehead et al., 2017 ) ( Vittecoq et al., 2018 ). The fitness costs associated with the possession of adaptations that prevent associated deleterious effects can sometimes be indirectly assessed by examining how individuals from polluted habitats perform when placed in non-polluted conditions.…”
Section: Costs At Different Organizational Levelsmentioning
confidence: 99%
“…There are several other examples of local adaptations in animals to cope with anthropogenic pollution ( Reid et al., 2016 ) ( Whitehead et al., 2017 ) ( Vittecoq et al., 2018 ). The fitness costs associated with the possession of adaptations that prevent associated deleterious effects can sometimes be indirectly assessed by examining how individuals from polluted habitats perform when placed in non-polluted conditions.…”
Section: Costs At Different Organizational Levelsmentioning
confidence: 99%
“…Species probably vary in their susceptibility to cancer due to variation in tolerance to environmental oncogenic factors [93] and variation in cancer defence mechanisms [94]. Interspecific variation in cancer risk may depend on life-history characteristics such as body size, growth rate and investment in sexual signal traits, but also on physiological mechanisms such as wound healing or the presence or depth of placentation (reviewed by Harris et al [94]).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the fastest rates of evolution globally take place in human-impacted habitats [97], and there is strong evidence of adaptive evolution in urban systems (reviewed by Donihue & Lambert [2]). From an applied perspective, Vittecoq et al [93] suggested that studying these species could inspire novel cancer treatments by mimicking the processes allowing these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In natural environments, the evolution of cancer suppressive mechanisms is weighted against other fitness-related functions (Jacqueline et al, 2017) (Vittecoq et al, 2018).…”
Section: How Could Dome S Ti C Ati On Le Ad To Novel Antic An Cer Amentioning
confidence: 99%